In vitro chondrogenic differentiation of human adipose-derived stem cells with silk scaffolds. - Kaplan, David, 1953-; Kim, Hyeon Joo.; Park, Sang-Hyug.; Durham, Jennah.; Gimble, Jeffrey M.; Dragoo, Jason L. (Tufts University. Tisch Library., 2016)
Human adipose-derived stem cells have shown chondrogenic differentiation potential in cartilage tissue engineering in combination with natural and synthetic biomaterials. In the present study, we hypothesized that porous aqueous-derived silk protein scaffolds would be suitable for chondrogenic differentiation of human adipose-derived stem cells. Human adipose-derived stem cells were cultured up to 6 weeks, and cell proliferation and chondrogenic differentiation were investigated and compared with those in conventional micromass culture. Cell proliferation, glycosaminoglycan, and collagen levels in aqueous-derived silk scaffolds were significantly higher than in micromass culture. Transcript levels of SOX9 and type II collagen were also upregulated in the cell-silk constructs at 6 weeks. Histological examination revealed that the pores of the silk scaffolds were filled with cells uniformly distributed. In addition, chondrocyte-specific lacunae formation was evident and distributed in the both groups. The results suggest the biodegradable and biocompatible three-dimensional aqueous-derived silk scaffolds provided an improved environment for chondrogenic differentiation compared to micromass culture.